PENGARUH SANKSI PERPAJAKAN, KESADARAN PERPAJAKAN, PELAYANAN FISKUS DAN TINGKAT PEMAHAMAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris Pada Kantor Pelayanan Pajak Pratama Jayapura) - Alfredo Johan Qui; Linda Yuliani Hutadjulu; Yohanes Cores Seralurin (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
Tax Sanctions, Tax Awareness, Fiscus Service and level of understanding are one of the factors that affect Taxpayer Compliance, so it needs to be improved. The purpose of this study was to determine the effect of tax sanctions, tax awareness, Fiscus Services and the level of understanding of taxpayer compliance. The data collection technique used in this research is to use a questionnaire with a total of 100 respondents as individual taxpayers. The population in this study is an individual taxpayer in the city of Jayapura. Data analysis in this study was carried out causatively, using multiple linear regression statistical tools with the help of IBM SPSS 25 software. This was to determine the description of the variables of Tax Sanctions, Tax Awareness, Fiscal Services and Level of Understanding of Individual Taxpayer Compliance. The results of this study prove that there is a significant influence between the variables of Tax Sanctions and Fiscal Services. Meanwhile, the Awareness and Understanding Level variables have no significant effect on taxpayer compliance.